PROBLEMS OF RESOURCE PLANNING DURING THE ERA OF DIGITAL ECONOMY - I. A. Brusakova; D. A. Belyanin (Дискурс)
Main problems and trends of resource planning during the era of digital economy are considered. The innovative infrastructure components of the digital enterprise resource planning are presented. The basic principles of human resources management in hi-technology manufacturing are given. An overview of existing methods and instruments of enterprise resource management and properties of corporate information systems of Russian and foreign production is provided. The scope of application and the time of implementation of corporate information systems for enterprise resource management have been analyzed.